Penyuluhan Tentang Pengembangan Literasi Baca Dan Numerasi Melalui Media Pop Up Box di Sekolah Dasar Se-Kecamatan Praya Lombok Tengah - Ida Bagus Kade Gunayasa; Moh. Irawan Zain; Ketut Sri Kusuma Wardani; Fitri Puji Astria (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2021)
In this era of modernization, the growth of reading and numeracy literacy is expected and required. Nevertheless, significant training is required to use pop-up box media to promote reading and numeracy literacy in a novel way. This community service activity takes the form of counseling and training, which can be divided into two categories: public lectures and guided exercises. Preparation, supplying tools and materials, implementation, and assessment are the processes that will be carried out in this activity in detail. Based on the outcomes of the activities, the implementation of this counseling activity proceeded successfully, and the activities were completed according to the timetable. Preparation, provision of tools and resources, implementation, and evaluation all went off without a hitch. The community service team supplied a response questionnaire relating to the activity's implementation to gauge the success of the activity, with the results of the activity's execution being excellent.